1997
DOI: 10.3109/09638289709166826
|View full text |Cite
|
Sign up to set email alerts
|

Posteroanterior spinal mobilization: state of the art review and discussion

Abstract: Posteroanterior spinal mobilization is a commonly used technique among physical therapists to diagnose and treat lower back pain patients. Human subjects and instruments have been used to test for the reliability of physical therapists' ability to detect intervertebral motion, but studies confirm unreliable testing. Despite documented efficacy of manual treatment the mechanical response to posteroanterior spinal mobilization is not well understood, and this has been emphasized in recent studies. Various modes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
2
20
0
1
Order By: Relevance
“…Based on such assessments patients of low back pain are commonly stated to have stiff spines. However, manual clinical assessment of PA stiffness has been demonstrated to be inaccurate (Simmonds et al, 1995;Bjornsdottir and Kumar, 1997) and with poor inter-rater reliability (Shirley et al, 2003;Matyas and Bach, 1985;Maher and Adams, 1994). Latimer et al (1996) reported patients of low back pain had increased PA stiffness.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on such assessments patients of low back pain are commonly stated to have stiff spines. However, manual clinical assessment of PA stiffness has been demonstrated to be inaccurate (Simmonds et al, 1995;Bjornsdottir and Kumar, 1997) and with poor inter-rater reliability (Shirley et al, 2003;Matyas and Bach, 1985;Maher and Adams, 1994). Latimer et al (1996) reported patients of low back pain had increased PA stiffness.…”
Section: Discussionmentioning
confidence: 97%
“…This device has been previously used and results published in peer reviewed literature (Simmonds et al, 1995;Bjornsdottir and Kumar, 1997). This electromechanical model was set on an treatment bed (Make: Hill Adjustable) and the loading block of the Therapeutic Spinal Mobilizer (TSM) was aligned over the vertebral spinous process and positioned appropriately to begin mobilization.…”
Section: Testing Reliability and Validity Of The Therapeutic Mobilizermentioning
confidence: 98%
“…23 These PPIM motion tests can be used to isolate each segment and to palpate segmental motion in all directions. 24 To perform PPIM motion tests, the evaluator passively moves the spine in a given direction, the spinal segment is palpated, and a judgment is made with respect to the amount of motion and end feel produced at that segment. 23 Mid-thoracic spine segments can demonstrate inconsistency in spinal mechanical behaviors.…”
mentioning
confidence: 99%
“…This technique evaluates passive segmental mobility, which is an indirect reflection of the integrity of periarticular structures (ie, disc, capsule, and ligaments). Even though this and other manual therapy methods have been used with varying levels of success to reduce pain and improve mobility, 1,2,7,9,13,15,16 it is unclear how this particular manual technique influences intervertebral motion of the lumbar spine.…”
mentioning
confidence: 99%
“…1,2,4,10,12,16 Posterior-toanterior (PA) mobilization is frequently employed to assess spinal mobility, and involves applying a force to a single vertebral spinous process with the individual lying in the prone position. This technique evaluates passive segmental mobility, which is an indirect reflection of the integrity of periarticular structures (ie, disc, capsule, and ligaments).…”
mentioning
confidence: 99%